Factors Affecting Internal Audit Effectiveness: Evidence from GCC Region - ABDELRAHIM, AYMAN ABDELLATIF (2023)
The role of the internal audit (IA) function in companies has evolved dramatically over the last two decades, and has become increasingly important to support audit committees and senior management. An effective IA provides audit committees and senior management with insights, assurance, and opportunities to improve the company’s internal control, risk management, and governance processes. However, IA effectiveness is influenced by many factors. This study aimed to examine factors that influenced the effectiveness of the IA function in publicly listed companies in the Gulf Cooperation Council (GCC) countries and examine the moderating effect of senior management support. Specifically, the factors that examined in this study were IA independence, IA size, IA staff competence, the relationship between IA and the audit committee, adopting a risk-based audit by IA, adopting a quality assurance and improvement program by IA, the role of IA in leading combined assurance implementation, cooperation between IA and external auditor, and senior management support. Existing literature emphasizes the need for research to examine factors that influence the effectiveness of the IA function, especially as few studies have been conducted on this topic. To the best of the researcher’s knowledge, this is the first empirical academic study in this area that covered all the GCC countries. This study contributes to the IA literature in different ways. First, by testing the relationship between the role of IA in leading combined assurance implementation and IA effectiveness. Second, by examining the moderating role of senior management support in the relationships between the aforesaid factors and IA effectiveness. Third, by testing new relationships, to the researcher’s knowledge, this is the first study that examines the relationship between IA role in leading combined assurance implementation and IA effectiveness, also this is the first study that examines the moderating role of senior management support between the relationship of IA effectiveness and the following factors: IA size; IA relationship with audit committee; adopting risk-based audit by IA; adopting a quality assurance and improvement program by IA; IA role in leading combined assurance implementation. In addition, this study expands the application of agency theory and institutional theory, also expands the literature and provides new insights into the factors that affect IA effectiveness and the moderating role of senior management support. This study employed a quantitative deductive approach. Data were collected by using a web-based questionnaire that was completed by 207 chief audit executives working in the GCC publicly listed companies. The results revealed that IA independence, IA size, IA staff competence, adopting a quality assurance and improvement program by IA, and the role of IA in leading combined assurance implementation were factors that positively and significantly affected IA effectiveness. Whereas, the relationship between IA and the audit committee, adopting a risk-based audit by IA, cooperation between IA and external auditor, and senior management support were factors that did not significantly affect IA effectiveness. Moreover, the results showed that senior management support, as a moderator between the examined factors and IA effectiveness, strengthened the relationships between IA effectiveness and IA independence, IA staff competence, and adopting a risk-based audit by IA. However, the results showed that senior management support as a moderator dampened the relationships between IA effectiveness and the relationship between IA and the audit committee, adopting a quality assurance and improvement program by IA, and the role of IA in leading combined assurance implementation. In addition, the findings suggested that senior management support did not play a moderating role in the relationships between IA effectiveness and IA size and cooperation between IA and external auditor. Furthermore, this study drew on the agency and institutional theories, and contributed to the internal auditing knowledge by applying these two different theories to identify factors that affect IA effectiveness and determine the importance of these factors in shaping IA effectiveness. Moreover, this study applies agency theory to explain the relationship between senior management and IA and explain the moderating role of senior management in reducing information asymmetry between senior management and the board through the support provided by senior management to IA function and interactions with factors that influenced IA effectiveness. In addition, this study contributes to institutional theory by emphasizing the isomorphic behavior of IA functions in companies and considering a broad set of factors and their influence on IA effectiveness. Finally, this study offered several policy implications for IA practitioners, audit committees, senior management, and external auditor, also offer policy implications for policy-makers, and regulators in the GCC countries that may help them to enhance corporate governance legislations.